Internalization Of Humanistic Values In The Learning Process For The Millennial Generation - Nurlaelah Nurlaelah (Jurnal Indonesia Sosial Teknologi, 2023)
In this era of globalization, Science and Technology (S&T) have become incredibly popular in daily life. S&T has brought people closer together and made the world more transparent. This situation poses a dilemma stemming from the remarkable progress of S&T. On one hand, this progress has made life more convenient for humans. On the other hand, our conscience raises concerns as we find ourselves in a situation that is no longer human-centric but rather technocentric. The millennial generation, born between the 1980s and the 2000s, is deeply intertwined with technological advancements, hence the term "millennial." They have experienced and actively participated in the development of technology. The millennials are the intelligent successors of the nation, continuously engaging with positive technological advancements. They possess positive attributes such as critical thinking, social media wisdom, creativity, and a desire to create harmonious relationships. However, they also exhibit negative traits such as communication difficulties, self-confidence issues, a sense of superiority, self-destructive tendencies, and a fear of job loss. One way to address the negative aspects observed in the millennial generation is through the internalization of humanistic values, particularly within the educational process at schools or in classrooms through humanistic education. Humanistic education as a whole provides a more comprehensive perspective, emphasizing an education that engages all dimensions and potential of humans, making individuals aware of their processes in becoming meaningful contributors to life, family, society, nation, and religion. The objective of this article is to describe the internalization of humanistic values in the millennial generation to counteract the potential negative aspects they might exhibit. The outcomes of this internalization are expected to shape millennials into intelligent, creative individuals who are human-centric in a techno-centric world